IMPLEMENTATION OF A WORDPRESS-BASED COMPANY PROFILE WEBSITE TO IMPROVE BRAND AWARENESS AT AMELIA FARM IN MAIWA DISTRICT, ENREKANG REGENCYKata Kunci: Brand Awarenesswordpress, Website Company Profile - M. Yusuf Firmansyah; Adam Latif; Rahman Yakub; Andi Riska Andreani Syafaruddin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to design and implement a WordPress-based company profile website to enhance brand awareness at Amelia Farm, a micro, small, and medium enterprise (MSME) engaged in layer chicken farming located in Maiwa District, Enrekang Regency. The research employs a descriptive qualitative approach using a case study method. The data consist of primary data collected through interviews with 10 informants, observations, and documentation of the implementation stages, as well as secondary data obtained from books, journals, scientific articles, and preliminary analysis using Google Analytics to measure user interactions with the website. The website design process follows the Agile method, which includes the stages of planning, design, development, and testing. Data analysis was conducted using descriptive qualitative methods to interpret the results of interviews, observations, and documentation, along with a simple analysis of Google Analytics data to measure the level of brand awareness. The results of the study show that the developed website was able to improve brand recognition and serve as an effective digital promotional medium. Data from Google Analytics recorded significant organic traffic and an increase in visits to the product pages, indicating prospective customers’ interest in Amelia Farm. Although user engagement still needs to be improved, the website has proven to provide an initial positive impact on brand visibility and recognition, and it has great potential to expand the market reach digitally.